Prevalencia de la violencia de género en los adolescentes del Cantón Paltas - Matailo Shanay, Geovanny Fernando (2024)
Physical, psychological or sexual violence against girls, boys and adolescents constitutes one of the main factors that interfere with the development of this age group. This public health problem continues to be present in society, under precepts that normalize and make it invisible, and In many cases they leave her unpunished. The present investigation is about the prevalence of gender violence in adolescents of the Paltas canton, for this the present analyzes this situation and denotes the existence of gender violence, it is a study with a descriptive, analytical and cutting approach. cross-sectional, in a non-probabilistic population sample of 91 adolescents to whom a survey was applied, resulting in 23% of young people in Paltas stating that they had been victims of gender violence on at least one occasion throughout their lives. their adolescence between the ages of 11 to 19 years. The type of violence that occurs most frequently is psychological, physical and verbal, with the home being the place where they most frequently suffer violence. In this way, it is concluded that there is a significant prevalence of this problem in the region, a situation that requires timely comprehensive attention that requires actions to prevent gender violence in adolescents. To comply, it will be coordinated with certain organizations of the Paltas canton, including the political tenure, the municipality and the cantonal board in order to provide information about this problem.